VALUE CO-CREATION DAN DIGITAL CUSTOMER EXPERIENCE : MENGUNGKAP KEPUASAN KONSUMEN BURGER KING MELALUI CUSTOMER ENGAGEMENT - Dyah Ika Kirana Jalantina; Maria Magdalena Minarsih (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to examine the influence of Value Co-Creation and Digital Customer Experience on Customer Satisfaction, with Customer Engagement as a mediating variable, among Burger King consumers in Indonesia. In an era of increasingly competitive fast food industry, customer satisfaction is a key factor for business sustainability. Value Co-Creation emphasizes the active role of consumers in creating shared value with the company, while Digital Customer Experience provides new interaction spaces through applications and social media. Customer Engagement is believed to strengthen emotional and functional relationships with the brand, thereby contributing to increased customer satisfaction.Using quantitative methods, a sample of 100 respondents who had made online purchases at Burger King Semarang was selected. Data were collected through questionnaires and analyzed using multiple linear regression and a mediation test. The results showed that Value Co-Creation and Digital Customer Experience had a positive and significant effect on Customer Satisfaction, both individually and simultaneously. Customer Engagement was proven to mediate the relationship between Value Co-Creation and Digital Customer Experience and Customer Satisfaction. The regression model used explained 53.5% of the variation in Burger King customer satisfaction.